Influence of physicians' seniority on head computed tomography use for patients with isolated vertigo/dizziness. Issue 9 (September 2020) - Tsai, Ming-Ta; Chang, Kung-Pin; Huang, Jyun-Bin; Cheng, Shih-Yu; Chiang, Charng-Yen; Cheng, Fu-Jen
Objective: Vertigo/dizziness is a common reason for emergency department (ED) visits. Emergency physicians (EPs) must distinguish patients with dizziness/vertigo owing to serious central nervous system (CNS) disorders. We aimed to evaluate the association between physician seniority and use of head computed tomography (CT) and ED length of stay (LOS) in patients presenting to the ED with isolated dizziness/vertigo. Methods: This retrospective cohort study included adult patients with non-traumatic dizziness/vertigo in the ED. EPs were categorized according to seniority: junior (less than 6 years' clinical experience), intermediate (7–12 years), and senior (≥12 years). Results: Among 2589 patients with isolated dizziness/vertigo, 460 (17.8%) received brain CT; 46 (1.78%) had CNS disorder as a final diagnosis. Junior and intermediate EPs ordered more CT examinations than senior EPs: (odds ratio [OR] = 1.329, 95% confidence interval [CI]: 1.002–1.769 and OR = 1.531, 95% CI: 1.178–2.001, respectively). Patients treated by junior and intermediate EPs had lower patient ED LOS (OR = −0.432, 95% CI: −0.887 to 0.024 and OR = −0.436, 95% CI: −0.862 to −0.011). Conclusions: We revealed different judgment strategies among senior, intermediate, and junior EPs. Senior EPs ordered fewer CT examinations for patients with isolated vertigo/dizziness but had longer patient LOS.